Rectal melanoma in a young man with symptoms mimicking spinal cord compression (Mediscope, 2022)
Rectal melanoma is a rare type of melanoma. Less than 3% of all forms of malignant melanomas with mucosal melanoma in the first place have been recorded. Low survival rates with poor prognosis are generally seen. Presentation of non-specific gastrointestinal symptoms results in delayed diagnosis and treatment. Rectal melanoma identified in a young man with signs that resemble spinal cord compression is not widely encountered.Mediscope 2022;9(1): 47-50